Wage Dispersion in the 1980's : Resurrecting the Role of Trade Through the Effects of Durable Employment Changes - Buckberg, Elaine (IMF Working Papers; Working Paper ;, 1995)
This paper finds that changes in durable manufacturing employment and investment in computer equipment can explain rising wage dispersion in the United States, measured in terms of the education premium. Reduced employment opportunities in durables production drive down the average wage for workers with only a high school education, thereby increasing the wage premium for college education. An innovation in this paper is the inclusion of investment in equipment as a proxy for skill-biased technical change. The rise in the technical skill premium could alone explain all of the rise in the college premium since 1979 were there no offsetting effects. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.